HUBUNGAN CEDERA KEPALA DENGAN DISORIENTASI PADA PASIEN KECELAKAAN LALU LINTAS DI IGD RS BHAYANGKARA MANADO - Bidjuni, Hendro; Rompas, Sefti (JURNAL KEPERAWATAN, 2017)
Abstract : According To the World Healt Organization (WHO) in 2008, traffic accidents became the 10th leading cause of death in the world with the number of deats is 1,21 million (2,1%), while according to the health profile of Indonesia in 2008 injury is the fourth major couse of death is (6,5%) for all ages after a stroke, tuberculosis, and hypertension. Disorientation is the inability of a person to know the position himself in relation to the time, place or specific objects in the enviroment. The purpose of the research to know the relationship of head injury with patient disorientation in ER Bhayangkara Hsopital. Research Methods used in tihis research is a Cross Sectional design, With a total of 38 samples of respondent.Techniques sampling is Accidental Sampling. Data analysis was done using the chi-square test. Views of the significance of 0.001 thus probability (significance) is smaller than 0.05. Conclusion There is a connection between head Injuries on the patient disorientation with traffic accidents. Expected results of this research can be used as reference material in the library and can add to the wealth of knowledge Especially in the field of health.Keyword : Head Injury, DisorientationAbstrak : Menurut World Health Organization (WHO) Tahun 2008, kecelakaan lalu lintas menjadi penyebab kematian ke-10 di dunia dengan jumlah kematian 1,21 juta (2,1%) sedangkan Menurut Profil Kesehatan Indonesia tahun 2008 cedera merupakan penyebab kematian utama keempat (6,5%) untuk semua umur setelah Stroke, TB, dan Hipertensi. Disorientasi adalah ketidaksanggupan seseorang untuk mengetahui posisi dirinya dalam hubungannya dengan waktu tempat, atau benda-benda tertentu di lingkungannya. Tujuan penelitian Untuk mengetahui hubungan cedera kepala dengan disorientasi pada pasien cedera kepala di IGD RS Bhayangkara. Metode Penelitian yang digunakan dalam penelitian ini adalah disain cross sectional dengan jumlah Sampel 38 responden. Teknik pengambilan sampel yaitu Accidental Sampling Analisa data dilakukan dengan menggunakan uji chi-square. Dilihat dari nilai signifikan atau nilai p = 0,001 dengan demikian probabilitas lebih kecil dari 0,05. Kesimpulan ada hubungan antara cedera kepala dengan disorientasi pada pasien kecelakaan lalu lintas.. Diharapkan hasil penelitian ini dapat dijadikan bahan referensi dalam kepustakaan dan dapat menambah kekayaan ilmu pengetahuan khusunya dibidang kesehatan.Kata Kunci : Cedera Kepala, Disorientasi